Algae production platforms for Canada's northern climate. (December 2017) - Pankratz, Stan; Oyedun, Adetoyese Olajire; Zhang, Xiaolei; Kumar, Amit
Abstract: Large resources are being invested globally in algae research in the anticipation that these microorganisms will become the "silver bullets" that lead to economic bio-renewable fuels, new food sources, and a host of high value products and simultaneously mitigate rising atmospheric CO2 levels. A great deal of research has been completed on strains of algae with the potential to produce high lipid yields that make the biomass suitable for biofuel production. Many production systems for algae cultivation continue to be developed for moderate and hot climates (e.g., USA, Europe, and Australia). The largest algae cultivation systems to date use open pond systems. These autotrophic systems, however, have limited applicability in Canada's northern climatic conditions. There is consensus that closed photobioreactor systems are required to control environmental conditions (including temperature), minimize evaporation and contamination, and augment the limited sunlight available during winter to generate consistent biomass yields for economically sustainable crops. Given the high capital and operating costs, however, many are skeptical that meaningful and economically sustainable algae cultivation can take place in Canada. This paper identifies nine scalable algae photobioreactor cultivation technologies that may suit Canadian northern climates. The information provides insights related to the developing algae industry in Canada as well as highlighting opportunities for further technological development specific to cold climates. Although the review demonstrates that exciting headway has been made, significant technological challenges remain and require that further innovations be developed.